Development of nanoparticles solid acid and bi-functional zirconia supported catalysts for production of biodiesel from waste cooking oil - Hamid, Fathelrahman Hamid Elhassan (2014)
Fossil-based oil has been the most important energy and fuel source since the mid of nineteenth century but there has been growing distress about an energy crisis caused by potential fossil-based oil depletion, high oil prices and the effect of gas emissions from petroleum on the environment. Thus, a need for a better energy security and an alarm about high petroleum prices has guided the scientific society to look for sustainable, renewable energy resources to decrease the reliance on fossil fuels. Biodiesel, which is considered as a potential substitute of fossil based-diesel fuel is commonly composed of the mono-alkyl ester of a long chain fatty acid that can be produced from vegetable oils, waste cooking oil and animal oil utilizing the esterification and transesterification reactions. However, competition between food and fuel economies towards the same oil resources may bring global crisis to the food supply and demand market. In this respect, the main goal of the research is to develop new nanoparticle solid acid catalysts that can be used in place of homogeneous catalysts for production of biodiesel from waste cooking oil. The new proposed catalytic system needs to be more eco-friendly, economically visible and technically applicable with a minimum level of complexity in terms of preparation and use. Moreover, the production of biodiesel from waste cooking oil offers a triplet aspect solution: economical, environmental and waste management. The developed nanoparticle solid acid and bi-functional catalysts are synthesized via precipitation and impregnation methods. The physico-chemical properties of the developed nanoparticle catalysts are characterized by using X-ray diffraction (XRD), temperature programming desorption (TPD-NH3/CO2), thermogravimetric analysis (TGA), energy dispersive spectroscopy (EDS), transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS), fourier transform infrared (FT-IR) and X-ray fluorescence (XRF) analyses. In addition, the catalytic activity of all synthesized catalysts for the production of biodiesel and the effect of variables, such as reaction temperature, reaction time, waste cooking oil/methyl alcohol molar ratio as well as the catalyst loading at the fixed stirring of 600 rpm on the biodiesel yield, has been evaluated. On the other hand, an examination of the reusability and leaching of ferric, manganese as well as sulphur species into the biodiesel is carried out. Moreover, extensive modification is done over a pre-selected catalyst sample with secured heterogeneous performance in an attempt to select the most active and industrially applicable catalysis system for biodiesel production. The central composite design (CCD) is used to design the experiments and the optimization of the process has been performed using response surface methodology (RSM) to understand the relationship between the factors and the yield of biodiesel besides that the optimum conditions for synthesis of the biodiesel is also determined. Results revealed that Fe/Mn-SO4 2-/ZrO2 is showed the best catalytic activity in the methanolysis of waste cooking oil to biodiesel. This is followed by the Fe/Mn- WO3/ZrO2 and Fe/Mn-WO3/MoO3 catalysts that appeared with the least catalytic activity. A good reusability of the catalysts with insignificant leaching of ferric, manganese and sulphur species into the biodiesel has also been obtained. According to the extensive modification on the surface of the Fe/Mn-SO4 2-/ZrO2, the ferric-manganese doped sulphated zirconia -16wt% SO4 2- nanoparticle bi-functional solid catalyst is found to be the best catalyst amongst the entire proposed developed nanoparticle heterogeneous catalytic system for the simultaneous synthesis of waste cooking oil based-biodiesel which attributed to its highest strength and active site density of both types, large surface area and a big pores size as well as the inconsiderable leaching of sulphur. The response surface methodology has been illustrated that the expected and experimental yield of waste cooking oil biodiesel based-biodiesel is found to be 97.0% and 97.2%, respectively, under the optimized conditions of 160 °C, 10.0 stoichiometric ratio, 3.0% wt/wt catalyst loading, reaction time of 4 h and stirring at 600 rpm. Furthermore, the physical and chemical characteristics of waste cooking oil-based biodiesel properties of the produced biodiesel are tested with compliance to EN14214 and ASTM D6751 standards.